Linguistic evidence of the theme of nature in a constellation of Robert Frost’s poems - Amira Hasan Ahmed; Monaliza Sabrini-Zin (Penerbit Universiti Kebangsaan Malaysia, 2025)
While Robert Frost is quite known for being a poet who wrote about nature, especially rural areas of New England in America, on trees, dark forests and nights, apples and apple harvesting, skies, stars, and even roads not taken, the use of such elements of nature in his poems and its contribution to the theme has not yet been adequately and collectively addressed. The current study focuses on analyzing a group of poems written by Robert Frost using AntConc and Lancbox (corpus linguistic toolkits) to provide linguistic evidence of the existence of the nature theme. This study examined how keywords, collocation, and colligation from different poems displayed the theme of nature. Based on a corpus stylistic approach, the study found that analyzing poems from different volumes shows the impact of the environment on the poet was positively and negatively associated with the poet’s convictions with nature. Robert Frost frequently clashes with nature in his themes of acceptance, loneliness, and terror. The poet's exposure to the rural landscape led him to appropriate many pictures from his surroundings and relate them to religious and universal ideas that form the core of his poems. In addition, because of its relatability and simplicity, Robert Frost's poetry has profoundly impacted many readers. This paper contributes to the current literature by revealing that Robert Frost’s poems portray nature, showing a connection between humanity and nature and emphasizing the impact of nature on people’s attitudes.